Uji Efektivitas Mikroorganisme Lokal Dari Kulit Nanas (Ananas comosus L.) Terhadap Pertumbuhan Dan Hasil Tanaman Mentimun (Cucumis sativus L.) - Khairani Khairani; Tuti Heiriyani; Noor Khamidah (Agroekotek View, 2019)
Local Microorganisms (MOL) can be produced from the fermentation of existing materials circled around and easy to be able to. One of the waste that can be considered as MOL is the skin of pineapple (Ananas comosus  L.) because it has a fairly high nutrient content (Rao, 1994). Therefore it is necessary to research its effectiveness on cucumber plants (Cucumis sativus L.). This research aims to determine the effectiveness of local microorganisms from pineapple skin and the proper dose in the provision of local microorganisms from the skin of pineapple to the growth and results of cucumber crops. This study uses a single-factor complete random draft (RAL) consisting of 4 treatments and 5 times repeated to get 20 units of trial. The treatment used is D0 (NPK 10 gr), D1 (MOL 75 ml/L water), D2 (MOL 100 ml/L water) and D3 (MOL 125 ml/L air) crop. The results showed that local microorganisms (MOL) of pineapple skin still have not effectively increased the growth and outcome of cucumber crops. Giving local microorganisms only affects the number of branches of cucumbers. The provision of chemical fertilizer NPK Pearls 10 gr/cropping has the best average results on the observation of the number of leaves, the number of branches, length of fruit and the number of fruits.